Gyrate atrophy of the choroid and retina: a case report - Büyüktortop, Nesrin; Alp, Mehmet Numan; Sivri, Serap; Coşkun, Turgay; Kural, Gülcan (The Turkish Journal of Pediatrics, 2011)
Gyrate atrophy is a rare metabolic disease characterized by hyperornithinemia, typical retinal and choroidal lesions, high myopia with marked astigmatism, early cataract formation, and autosomal recessive inheritance pattern. In this paper, we describe a 12-year-old boy presenting with high myopia and gyrate fundus lesions, in addition to 10-times elevated serum ornithine level.